Ho Chi Minh City implements resolution No. 98/2023/QH15 - difficulties, inadequacies and recommendations - Ta Thi Thanh Tam (Journal of State Management, 2024)
Resolution No. 98/2023/QH15, dated June 24, 2023, by the National Assembly on pilot implementation of particular policies for the development of Ho Chi Minh City has granted the city various new mechanisms and policies, creating momentum for its growth and maintaining its position as the leading economic hub of the country. One year after the Resolution took effect, in addition to the advantages, the city faced numerous difficulties and inadequacies in its implementation. This study analyzes and clarifies the challenges faced by the Ho Chi Minh City government in implementing Resolution No. 98/2023/QH15, thereby proposing several recommendations to effectively execute the Resolution and fully leverage the city's potential and advantages.